Melanocyte proliferation in wounded skin in vitro: a histological and immunohistochemical analysis - Petersen, Morea (Division of Cell Biology, 2018)
Wounding of skin initiates a complex series of overlapping cellular events that culminates in the formation of a scar. The negative consequence of most cutaneous scars is the lack of adequate repigmentation of the neoepidermis. In order to effect successful wound healing by restoration of effective skin barrier function, keratinocytes must proliferate and migrate to cover the gap created by the wound in an efficient and timeous manner. Melanocytes are not thought to actively participate in wound repair and closure, since they are primarily responsible for maintenance of normal skin pigmentation. Mechanisms of keratinocyte migration during the re-epithelialisation phase of cutaneous wound healing have been well documented. However, it is not clear how melanocytes contribute to neoepidermis formation and repigmentation. Provision of an optimal epidermal milieu would enable restoration of pigmentation of cutaneous scars for a satisfactory cosmetic outcome. This dissertation contributes to the understanding of melanocyte participation and proliferation during re-epithelialisation of skin using an in vitro skin organ culture model of wound healing. To determine whether the culture model used in this study was reliable, skin explants were cultured over a period of 12 days, fixed and processed for histological analysis. By measuring the lengths of the developing epidermal tongues, it was noted that epiboly was the initial event that occurred at the wound edges. After day two of culture, growth of the epithelial tongues was observed from the wound edges, which peaked at day five. The length of the epidermal tongues remained constant for the remaining culture period up to day twelve, at which stage complete wound closure was observed in some samples. Histological analysis of the tongues revealed that the cultured skin remained viable for the duration of culture period. To establish to what extent keratinocyte proliferation contributed to the growth of the tongues, immunohistochemical staining using the proliferation marker, Ki67, was used. Results show that after an initial lag phase, with no detectable cell proliferation at the wound edges, dividing keratinocytes were seen at day two post-wounding. The number of dividing keratinocytes peaked at day five, where after the numbers remained constant until day twelve of culture. This result supports the validity of the culture model. To uncover whether melanocytes re-enter the neoepidermis during wound during re-epithelialisation, the number of melanocytes per unit of basement membrane was determined using immunohistochemical staining. The melanocyte-specific marker, MART-1/MelanA, was used in conjunction with the proliferation marker, Ki-67, in an optimised dual immunolabelling protocol {Petersen, 2012 #397} to establish whether melanocytes proliferate during re-epithelialisation of wounds. Melanocytes along the basal layer of the epithelial tongues and in the normal epidermis were located and counted. Basal melanocytes (MelanA+) were seen from day two onwards in the normal epidermis and from day five onwards in the developing epidermal tongues. However, at days ten and twelve of the culture period. dividing melanocytes (Ki67+/MelanA+) were seen in the epidermis in locations: proximal to the wound area, at the wound edge and in the developing tongues. This result suggests that melanocyte entry into the wound is delayed until after keratinocyte proliferation has brought about the beginning of neoepidermis formation and growth. This result also demonstrates the proliferation potential of differentiated melanocytes and that de-differentiation of melanocytes can occur under favourable culture conditions as can be seen in this culture model.